TextCrunch / Noorezatty Mohd Yusop … [et al.] - Mohd Yusop, Noorezatty; Khairol Azmi, Nurul Nisa’; Abdul Wahab, Nurul Aini; Mohd Rosli, Intan Nur Izzaty (Faculty of Computer and Mathematical Sciences, 2023)
TextCrunch is a cutting-edge web application that has been specifically created to enrich the process of teaching and learning text mining. It provides a range of valuable benefits to educators, researchers, and learners alike. This innovative tool serves as an intuitive educational resource, making it an indispensable asset for individuals in academia and beyond. By operating on the Shiny framework, TextCrunch offers a user-friendly and comprehensive interface that simplifies the complex world of text data analysis. One of the key features of TextCrunch is its ability to allow users to upload text data and generate real-time results. This means that educators, researchers, and learners can easily analyze their text data and obtain immediate insights. The application offers various visualizations, such as word clouds, frequency plots, topic modeling, and more. These visualizations enable users to explore and understand their text data in a more interactive and meaningful way. By providing real-time results, TextCrunch empowers users to make informed decisions and draw accurate conclusions based on their data analysis. TextCrunch's user-friendly interface is designed to accommodate users with varying levels of expertise in text mining. Whether you are a beginner or an experienced researcher, this web application offers a seamless experience that simplifies the process of analyzing text data. The intuitive design ensures that users can navigate through the various features and functionalities with ease, allowing them to focus on the analysis itself rather than getting lost in technicalities. In summary, TextCrunch is an invaluable tool for anyone involved in text mining, be it educators looking to enhance their teaching methods, researchers seeking to gain new insights from their data, or learners aiming to develop their skills in text analysis. With its user-friendly interface and real-time results generation, this innovative web application is poised to revolutionize the field of text mining and contribute significantly to the advancement of knowledge in various disciplines.